Co-infection of bacterial and parasitic pathogens including the brain myxosporean Zschokkella auratis in farmed striped murrel Channa striata (Bloch, 1793) causing large scale mortality - Paul, Anirban; Pattanayak, Sabyasachi; Sahoo, Manoj Kumar; Rajesh Kumar, P.; Kumar, Rajesh; Sahoo, P. K. (Indian Journal of Fisheries, 2020)
Co-infections in fish by the wide array of pathogens have been little researched, although such infections are commonly noticed in nature. A murrel farm recorded 100% mortality in adults of Channa striata within 3-4 days of infection during winter. The clinical signs included cloudy eyes, excess mucus secretion, haemorrhages on the body, lethargy and anorexia in C. striata before mortality. Heavy infection with Ichthyophthirius multifiliis on the body surface and Zschokkella auratis, a new myxosporean to this country, in the brain tissue were detected by wet mount microscopy and 18s rDNA sequencing, respectively. Histological sections of the brain also demonstrated the presence of myxosporean cyst. Examination of eye fluid and eye tissue revealed the presence of bacterium Acinetobacter baumannii and blood samples containing Aeromonas sobria and Klebsiella pneumoniae were detected under 16s rDNA and species-specific PCRs followed by sequencing. Interestingly, samples collected from infected fishes also revealed multiple parasitic pathogens viz., Epistylis sp., Trichodina sp., Argulus siamensis and Ergasilus sp. Thus, it was delineated that prolonged low water temperature might be playing one of the influential roles in creating stress in fish, thus making the fish susceptible to complicated or mixed bacterial andparasitic infections.Keywords: Acinetobacter baumannii, Channa striata, Co-infections, Mass mortality, Zschokkella auratis